The problem of professional ethics - Rohr, John A
The article explains why professional statements tend to be self-serving and examines the ethics of public administration in the light of this explanation. In so doing the author has tried to illuminate an aspect of professionalism that should be of particular interest to the public administration community
Keywords: Public Policy; Public Administration; Professions; Ethics